BANK EFFICIENCY ANALYSIS ON THE PERFORMANCE OF ISLAMIC BANKING IN INDONESIA (Case Study of Islamic Commercial Banks Listed on the IDX for the Period 2014-2018) - Jashinta Efril; Estu Widarwati; Nunik Nurmalasari (STIESA Press, 2021)
The purpose of this study is to determine the efficiency and performance of Islamic banking in Indonesia and the effect of the relationship between efficiency on the performance of Islamic banking in Indonesia. This type of research is descriptive. With the research object is the financial statements of 11 Islamic banks in Indonesia. The data analysis method used is Data Envelopment Analysis (DEA), ratio analysis, and panel data. The results showed that based on the DEA analysis, the overall average of Islamic banks reached an efficiency of 95.1%, and in several periods the 11 banks had an efficiency level of 100%. In the ROA ratio analysis, it shows that Islamic banks are in bad condition, the NIM ratio analysis shows that Islamic banks are in good condition. The analysis of the effect of the DEA analysis with the ROA and NIM ratios shows that the ROA ratio is not significant and has a negative effect on DEA. The NIM ratio has a positive and significant effect on the DEA analysis. Sharia banking listed on the IDX 2014-2018 should be able to manage time, funds, costs as best as possible. As well as avoiding risks and interests between investors or funders so that banks avoid Increasing and Decreasing. The next researcher should be able to add other variables such as other ratio performance variables.